1. Rearrange: 3ln(y) = 6-18ln(x) = 6ln(e) - 18ln(x)
Now what do you know about your log laws that will allow you to simplify the RHS?
2. If they're the same base yes. If not you may need to use the change of base rule
I was having trouble with the following:
1)An expression for y in terms of x by rearranging 18loge(x)=6-3loge(y).
2) solutions for x in (log6(x))^2+4log3(6)+6=0.
-Do i interpret this one as a quadratic equation? If so, the solutions should be 3 and 2, but from there what do i do?
-thanks.
Not really sure what they are after here, but is this correct?
18loge(x)=6-3loge(y)
restated as: 18*ln(x) = 6 - 3*ln(y)
express in terms of y=
18*ln(x) + 3*ln(y) = 6
ln(x^18y^3) = 6
e^6 = x^18y^3
y^3 = e^6/x^18
y = cube root(e^6/x^18)